Elementary school teachers’ perceptions of the potential of metaverse technology as a transformation of interactive learning media in Indonesia - Rachmadtullah, Reza; Setiawan, Bramianto; Wasesa, Andarmadi Jati Abdhi; Wicaksono, Jatu Wahyu (International Journal of Innovative Research and Scientific Studies, 2023)
Currently, there are many technology-based learning methods that can be used in the teaching and learning process for effective learning situations. The metaverse is a topic that is being widely discussed around the world. Metaverse technology is the concept of combining the virtual world with the real world through the internet. However, the development of metaverse technology in Indonesia’s education field is still rarely carried out. Therefore, this research aims to determine how elementary school teachers in Indonesia perceive the potential of metaverse technology as a learning media transformation. The research method used by researchers is descriptive with a qualitative approach. Descriptive research is research that describes the actual situation regarding the importance of the metaverse for teachers in elementary schools. The participants in this study were twenty elementary school teachers who had good technological skills. The data was collected through observation and interviews. The results of this study show that elementary school teachers are interested in using the metaverse as a learning medium. For teachers, one of the options for improving learning performance is to use the metaverse as a tool or as a new learning and teaching style. The use of the metaverse does not mean that the teacher has to change conventional teaching methods but rather assists the teacher in conveying material to students effectively.